Analisis Pengelolaan Arsip Dinamis Aktif melalui Sistem E-Arsip di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Surabaya - Afrila Devintan Triwulansari; Dian Arlupi Utami (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This research is motivated by the importance of electronic-based active records management in supporting effective government administration. The Surabaya City Human Resources Development Agency (BKPSDM) has implemented an e-Archive system to manage electronic records; however, several challenges still hinder its optimal utilization. This study aims to analyze the management of active records through the e-Archive system based on the electronic records life cycle proposed by Read and Ginn in Muhidin and Winata (2018), which consists of creation and storage, distribution and use, maintenance, and disposition. This study employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The findings indicate that the e-Archive system provides adequate features, but its implementation has not been optimal across all stages of records management. Record creation and storage remain centralized in the Secretariat account and are not consistently carried out by all work units. System utilization in distribution and use is still limited. Archive Retention Schedule and filing features have not been fully utilized in the maintenance stage. Furthermore, records disposition is still conducted manually outside the system. Therefore, active records management through the e-Archive system at BKPSDM Surabaya has not been implemented optimally and comprehensively throughout the electronic records life cycle.